Combined gas conditioning and cleaning for reduction of tars in biomass gasification. (February 2018) - Pallozzi, V.; Di Carlo, A.; Bocci, E.; Carlini, M.
Abstract: Tar production in a biomass gasification process is one of the biggest issues for this technology and, thus, gas conditioning represents a key role in its development. The aim of this work is to evaluate the removal efficiency, besides the stability during the time, of a gas conditioning and cleaning section in a combined configuration. In particular, the primary treatment step consists in a secondary bed reactor of dolomite, before of an exhausted vegetable oil scrubber. They were analysed for several hours of operation (12 h), coupled to a bench-scale gasification reactor. It was obtained that the combined system provides reduction of total tars (MW > C7 H8 ) equal to 97%, leading to a producer gas dew point temperature of 17 °C. On the contrary, when only cleaning action of scrubber media is considered, saturation of oil occurs after only 1.5 working hours. In the same time, when only conditioning system of dolomite guard bed is considered, tars reduction is still high, even after 14 working hours, but dew point temperature is 56 °C. The combined gas conditioning and cleaning system resulted to be the best solution in terms of removal efficiency and stability. Highlights: Vegetable oil scrubber and dolomite guard bed for biomass gasification tar removal. Combined cleaning and conditioning system tested for 12 h of operation. Tars reduction of 97% (MW > C7 H8 ) and dew point temperature of 17 °C. Durable, efficient and sustainable cleaning system for syngas exploitation. Crucial technology for biomass gasification plants development.